Molecular Determinants of Enterotoxigenic Escherichia coli Heat-Stable Toxin Secretion and Delivery - Zhu, Yuehui (Infect Immun, 2018)
Enterotoxigenic Escherichia coli (ETEC), a heterogeneous diarrheal pathovar defined by production of heat-labile (LT) and/or heat-stable (ST) toxins, causes substantial morbidity among young children in the developing world. Studies demonstrating a major burden of ST-producing ETEC have focused interest on ST toxoids for ETEC vaccines. We examined fundamental aspects of ST biology using ETEC strain H10407, which carries estH and estP genes encoding STh and STp, respectively, in addition to eltAB genes responsible for LT. Here, we found that deletion of estH significantly diminished cyclic GMP (cGMP) activation in target epithelia, while deletion of estP had a surprisingly modest impact, and a dual estH estP mutant was not appreciably different from the estH mutant. However, we noted that either STh or STp recombinant peptides stimulated cGMP production and that the loss of estP was compensated by enhanced estH transcription. We also found that the TolC efflux protein was essential for toxin secretion and delivery, providing a potential avenue for efflux inhibitors in treatment of acute diarrheal illness. In addition, we demonstrated that the EtpA adhesin is required for optimal delivery of ST and that antibodies against either the adhesin or STh significantly impaired toxin delivery and cGMP activation in target T84 cells. Finally, we used FLAG epitope fusions to demonstrate that the STh propeptide sequence is secreted by ETEC, potentially providing additional epitopes for antibody neutralization. These studies collectively extend our understanding of ETEC pathogenesis and potentially inform additional avenues to mitigate disease by these common diarrheal pathogens.